1983
DOI: 10.1113/expphysiol.1983.sp002735
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for the Inhibitory Neurotransmitter in Bovine Tracheal Smooth Muscle

Abstract: SUMMARYThe effect of inhibitory nerve stimulation on the mechanical, membrane potential and membrane conductance responses of isolated bovine tracheal smooth muscle has been studied.Membrane responses were measured in a sucrose-gap apparatus. In order to record inhibitory responses, it was necessary to increase tone in the preparation by applying a drug such as histamine. When tone was raised, repetitive field stimulation of intrinsic nerves caused depolarization and contraction, followed by relaxation and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The present experiments have shown that the guineapig trachealis resembles that of the ox (Kirkpatrick, 1981;Cameron et al, 1983) and dog (Suzuki et al, 1976;Ito & Tajima, 1982) in that the inhibitory action of isoprenaline is accompanied by hyperpolarization.…”
Section: Involvement Ofp1-adrenoceptors In Isoprenaline-induced Hypermentioning
confidence: 73%
See 1 more Smart Citation
“…The present experiments have shown that the guineapig trachealis resembles that of the ox (Kirkpatrick, 1981;Cameron et al, 1983) and dog (Suzuki et al, 1976;Ito & Tajima, 1982) in that the inhibitory action of isoprenaline is accompanied by hyperpolarization.…”
Section: Involvement Ofp1-adrenoceptors In Isoprenaline-induced Hypermentioning
confidence: 73%
“…In the trachealis of the ox and dog the inhibitory It also seems to represent an increase in membrane effects of adrenaline or isoprenaline are associated conductance (presumably to K+) because electrotonic with hyperpolarization of the muscle cells (Suzuki et potentials evoked by the passage of current pulses are al., 1976; Kirkpatrick, 1981;Ito & Tajima, 1982; reduced in amplitude during the hyperpolarization Cameron et al, 1983). This hyperpolarization seems to (Ito & Tajima, 1982;Cameron et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Although the neurotransmitters involved in this 'third' nervous system are not yet certain, there is some evidence that neuropeptides may be involved (Barnes, 1984). Non-adrenergic inhibitory nerves have been demonstrated in the lung, particularly in airway smooth muscle (Richardson, 1981) and there is evidence that vasoactive intestinal peptide (VIP) might be a neurotransmitter since VIP has been localised in these nerves by immunocytochemical methods (Dey et al, 1981;Laitinen et al, 1985) and VIP has been found to relax partially airway smooth muscle (Said, 1982;Cameron et al, 1983;Palmer et al, 1985). A NANC inhibitory response has also been 'Author for correspondence at: Department of Clinical Pharmacology,Cardiothoracic Institute,Fulham Road,London SW3 6HP demonstrated in the pulmonary artery of several species (Hamaski et al, 1983b;Frank & Bevan, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It is in keeping with the general concept of mediator release that calcium channels should be important in this system too but, as far as I know, nobody has demonstrated that peptide release depends upon the presence of calcium and might be inhibited by calcium-antagonists. The most likely candidate for the NAIS bronchodilatory system is vasoactive intestinal polypeptide (VIP) (Cameron et al, 1983) and it would be of con- Of great current interest is the demonstration that stimulation of sensory afferent fibres in the airways (including the nose) can set up local reflexes involving the release of the mediator substance P, which may have a bronchoconstrictor action as well as a secretagogue effect (Lundberg & Saria, 1983;Karlsson & Persson, 1983). Again, the discussion must centre on analogy with other systems.…”
Section: Vagal Nonadrenergic Inhibitory System (Nais)mentioning
confidence: 99%